An "off–on"-type electrochemiluminescent immunosensor based on resonance energy transfer and a liposome-assisted strategy for signal amplification. (23rd March 2023) - Wang, Yu-Ling; Fu, Yi-Zhuo; Xiao, Hui-Jin; Wu, Pan; Ren, Shu-Wei; Cao, Jun-Tao; Liu, Yan-Ming
Abstract : ECL-RET in BP/MnO2 nanocomposites coupled with glutathione-loaded liposomes for the immunoassay of proteins. Abstract : An "off–on"-type electrochemiluminescence (ECL) system for a myoglobin (Myo) assay was proposed by coupling a resonance energy transfer (RET) strategy with functional liposomes as probes. Specifically, black-phosphorus nanosheets (BP NSs), as energy-donors, were introduced into an ECL system, and MnO2 NSs (energy-acceptors) were reduced on the surface of BP NSs in situ to form the BP/MnO2 nanocomposites. Thanks to a perfect spectral match between BP NSs and MnO2 NSs, efficient ECL-RET occurred in BP/MnO2 nanocomposites. Glutathione (GSH)-loaded liposomes (as probes for the regulation and amplification of signals) were immobilized in a 96-well plate through a sandwich immunoreaction. The abundant GSH lysed from liposomes could reduce MnO2 to Mn 2+ effectively and destroy the RET, thus regulating the degree of recovery of the ECL signal from BP NSs. The absence and presence of GSH generated the "signal-off" and "signal-on" states of the BP/MnO2 nanocomposites-based ECL system. The amount of Myo could be estimated by the degree of recovery of the signal. Benefiting from these phenomena, a good linear relationship ranging from 1.0 × 10 −13 to 1.0 × 10 −7 g mL −1 was found and the limit of detection was down to 2.5 × 10 −14 g mL −1 for Myo. Furthermore, the ECL system revealed a favorable performance for the determination of Myo in samples of human serum.